2011
DOI: 10.1371/journal.pone.0021253
|View full text |Cite
|
Sign up to set email alerts
|

A Micro RNA Processing Defect in Rapidly Progressing Idiopathic Pulmonary Fibrosis

Abstract: BackgroundIdiopathic pulmonary fibrosis exhibits differential progression from the time of diagnosis but the molecular basis for varying progression rates is poorly understood. The aim of the present study was to ascertain whether differential miRNA expression might provide one explanation for rapidly versus slowly progressing forms of IPF.Methodology and Principal FindingsmiRNA and mRNA were isolated from surgical lung biopsies from IPF patients with a clinically documented rapid or slow course of disease ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 63 publications
(91 reference statements)
6
87
2
2
Order By: Relevance
“…Classical gene expression profiling studies have progressed in IPF from characterizations of small numbers of human or mouse lung samples to analyses of large cohorts that have led to identification of multiple relevant genes (92)(93)(94)(95). Progress has been made in novel profiling of IPF as well: mechanistically relevant changes in microRNA expression profiles in IPF lung have been described (96)(97)(98), and studies aimed at determining the lung methylome are ongoing (99,100). Investigators can now access the Lung Genomics Research Consortium website (http://www.lung-genomics.org/lgrc) and download mRNA, microRNA, methylation, and SNP profiles of carefully phenotyped IPF lungs.…”
Section: Profiling Of Pulmonary Fibrosis Using Novel Techniquesmentioning
confidence: 99%
“…Classical gene expression profiling studies have progressed in IPF from characterizations of small numbers of human or mouse lung samples to analyses of large cohorts that have led to identification of multiple relevant genes (92)(93)(94)(95). Progress has been made in novel profiling of IPF as well: mechanistically relevant changes in microRNA expression profiles in IPF lung have been described (96)(97)(98), and studies aimed at determining the lung methylome are ongoing (99,100). Investigators can now access the Lung Genomics Research Consortium website (http://www.lung-genomics.org/lgrc) and download mRNA, microRNA, methylation, and SNP profiles of carefully phenotyped IPF lungs.…”
Section: Profiling Of Pulmonary Fibrosis Using Novel Techniquesmentioning
confidence: 99%
“…More recently, the abnormal expression of mRNAs has also been associated with the pathogenesis of both cancer and IPF. mRNAs are short nonprotein-coding RNA strands that may regulate the expression of related target genes involved in the control of different processes linked to carcinogenesis, such as tumour growth, invasion and metastasis [24][25][26]. Recently, it has been shown that ,10% of mRNAs are abnormally expressed in IPF, some of them, such as let-7, miR-29, miR-30 and miR-200, are significantly downregulated, while miR-155 and miR-21 are instead upregulated.…”
Section: Epigenetic and Genetic Abnormalities In Ipf And Cancermentioning
confidence: 99%
“…The IPF patient population was further subdivided into slow and rapid progressors as previously described [26]. We noticed a decrease in the epithelial markers keratin 18 and keratin 19 in both slow and rapid progressors ( Figure 5(a)).…”
Section: Alterations In Epithelial Mesenchymal and Apoptotic Markersmentioning
confidence: 62%